Kendala dan Solusi dalam Proses Pembelajaran Anak Autisme di SD Negeri Keleyan 1 Bangkalan - Teresia Anjelina Sembiring; Nova Estu Hartiwi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Education for children with autism requires specialized approaches tailored to their individual needs. This study aims to comprehend the challenges and solutions associated with educating autistic children at SD Negeri Keleyan 1 Bangkalan. The employed research methodology is descriptive qualitative, utilizing a case study approach. Data was gathered through interviews with the special education teacher for autistic children. The interview findings revealed that autistic children at SD Negeri Keleyan 1 Bangkalan face two primary learning obstacles: low attention span and rapid mood swings. The teacher implements solutions such as waiting for the child's mood to improve before starting the lesson, providing entertainment, and asking parents to review the material at home. Enhancing the quality of education for autistic children necessitates ongoing efforts from various stakeholders, including teacher training, curriculum development, augmenting learning materials, fostering communication with parents, and providing emotional support to the children.